Head and heart : perspectives from religion and psychology - Watts, Fraser N.; Drumbeck, Geoff (Templeton Press, 2013)
Theologians and religious figures often draw a distinction between religion of the '"head" and religion of the "heart," but few stop to ask what the terms "head" and "heart" actually denote. Many assume that this distinction has a scriptural basis, and yet many Biblical authors used the word "heart" as a synonym for "mind." In fact, there isn't a strict separation of the two concepts until the modern period, as in Pascal's famous claim that "the heart has its reasons that reason can not know." Since then, many other philosophers and theologians have made a similar distinction.